Sensorless collision detection and control by physical interaction for wheeled mobile robots - Doisy, Guillaume (2012 7th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2012)
In this paper, we present the adaptation of a sensorless (in De Luca's sense [1], i.e., without the use of extra sensors,) collision detection approach previously used on robotic arms to mobile wheeled robots. The method is based on detecting the torque disturbance and does not require a model of the robot's dynamics. We then consider the feasibility of developing control by physical interaction strategies using the described adapted technique.